Complementary and alternative medicine use in patients with gynecological cancers in Europe. (1st January 2006) - Molassiotis, A.; Browall, M.; Milovics, L.; Panteli, V.; Patiraki, E.; Fernandez-Ortega, P.
Abstract : The aim of the present study was to assess the use of complementary and alternative medicine (CAM) specifically in women with gynecological cancer. The design of the study was of a descriptive cross-sectional survey using a 27-item questionnaire. The study was conducted in 11 countries in Europe as part of a larger project. Data were available from 72 gynecological cancer patients. Among the participants, 40.3% used CAM after the diagnosis with cancer. The most popular CAM modalities used were herbal medicine (34.5%), relaxation techniques (21.4%), and vitamins/minerals (20.7%). A very high level of satisfaction with CAM use was reported. Patients used CAM to increase the body's ability to fight the cancer or to improve physical and emotional well-being. The main sources of information about CAM were informal (friends/family or the media). It is important to discuss CAM use with gynecological cancer patients, as they frequently use it and such use may have implications for clinical practice.